The possibility of applying digital elevation model in geomorphological studies (Journal of Geography and Environmental Management, 2019)
The article deals with the general concept of digital elevation models, the types of GIS formats, information sources forDEM creation (digital elevation model). Examples of possible applications in geomorphological research are presented.